Interaction with members of logistics systems at moving the material flow - Харченко, Віктор Федорович; Санько, Ярослав Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Function of a coordination of work of the sender, transport and the consumer is defined at moving of a material flow. The result of researches is the offered approach to working out of schedules of coordination of work of vehicles, drivers and points of cargo handling works